Effective Simulation Methods Improve Student Skills in Performing Basic Life Support - Hadi Kusuma Atmaja; Mira Utami Ningsih; Erien Luthfia; Muhammad Hasbi; Satriya Pranata (Jurnal Ilmiah Kesehatan, 2023)
Almost ten thousand people are affected by cardiac arrest, and the prevalence tends to increase every year in Indonesia. Nursing students need to have skills in performing basic life support (BLS) to increase the survival rate of patients with cardiac arrest inside or outside the hospital. An effective method for facilitating students in gaining such skills is educational simulation. This study aims to identify the effectiveness of the simulation method in improving students' skills in providing BLS. This is a quantitative quasi-experiment with a pre-posttest design. The sample is all fourth-year students in Nursing at Poltekkes Kemenkes Mataram who have had emergency classes in the previous semester. Data were collected using observation sheets and analyzed using the Wilcoxon Signed Rank Test to identify students' skills before and after they were given educational simulations. Before the educational video method was implemented, most respondents had insufficient skills in carrying out BLS, with 11 people (55%) falling into this category. Only two respondents (10%) demonstrated good skills in conducting BLS. After the simulation, all respondents acquired the skills to perform BLS in the "good" category, with 32 people (82%) exhibiting these skills. There were no respondents who had sufficient or poor BLS skills. Educational simulation significantly influenced students' skills in performing BLS (p=0.000). It can be concluded that the simulation method was effective in improving the students' skills in performing BLS. Educational simulation of BLS can be applied as an alternative method in the learning process.